Utilization of MADS-Box genes for agricultural advancement: current insights and future prospects - Anupam Tripathi; Kiran Vishwakarma; Sandhya Tripathi; Jyoti Singh Jadaun; Amrit Kumar Nayak (Molecular Biology Reports, 2026)

Quinone-fused diazepine π-conjugated carbon black: A chemically induced, topological-defect like engineered platform for ultrastable redox activity and ultrasensitive electrocatalytic sensing of ascorbic acid - Kumar Sandhya; Sugumar Monisha; Rajan Reshma; Krishnan Ashokkumar; K. Sriraghavan; Annamalai Senthil Kumar (Chemical Engineering Journal, 2026)

Microphysical evolution of fog: Transition from haze to fog in Delhi - Prasanna Lonkar; Sandhya Jose; Sandeep Wagh; Pooja Pawar; Sumit Kumar; Suresh Gosavi; Akash S. Vispute; Sachin D. Ghude (Atmospheric Environment, 2026)

Efficacy of seed priming through different plant extracts on seed germination of Naga-King Chilli (Capsicum chinense Jacq.) - Kime Tare; Rajesh Kumar; Amrit Lamichaney; Tshering Lhamu Sherpa; Koushik Baruah; Lomash Sharma; Sandhya Lamichaney (Acta Physiologiae Plantarum, 2026)

Electrospun nanofiber-based platforms for mycotoxins sensing: Recent advances and future directions - Vanish Kumar; Sandhya Ruhal; Ki-Hyun Kim (Food Chemistry, 2026)

Comparative Seasonal Proteome Profiling of the Liverwort Plagiochasma appendiculatum Reveals Molecular Strategies of Acclimation in its Natural Habitat - Vishal Kumar Jha; Akanksha Srivastava; Sandhya Yadav; Suvajit Basu; Subhankar Biswas; Kritika Tripathi; Neha Chaurasia; Sushil Kumar Singh; Vaibhav Srivastava; Yogesh Mishra (Plant Molecular Biology Reporter, 2026)

Screening and optimisation of crude exopolysaccharide production by marine Brevibacterium sp. JAB08 isolated from the jellyfish Chrysaora sp. from the coastal waters of Goa - Balaji Vaishnavi; R. Amal; Biraja Kumar Sahu; S. V. Sandhya (Antonie van Leeuwenhoek, 2026)

ARF Gene Family: Expression Dynamics, Signalling, and Importance in Seed Development - Kumari Arpita; Sandhya Sharma; Anshika Tyagi; Arvind Yadav; Sandeep Kumar; Rupesh Deshmukh; Robert M Stupar; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Integrative transcriptome and long non-coding RNA analysis to decipher the molecular basis of cleistogamy in pigeonpea (Cajanus cajan (L) Millsp) - Palak Gupta; Harsha Srivastava; Kuldeep Kumar; Kishor U. Tribhuvan; Tanvi Kaila; Swati Saxena; Kumar Durgesh; Sandhya Sharma; Kishor Gaikwad (Planta, 2026)

Development of in vitro germination and cryopreservation protocols of pollen in wild Lathyrus species to overcome longevity and asynchronous flowering constraints - Rinky Resma Panda; Padmavati G. Gore; Aishmita Gantait; Esha Singh; Mahesh Rao; S. Rajkumar; Shiv Kumar; Kuldeep Tripathi; Sandhya Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Stability and climate resilience of garlic genotypes under organic conditions of Sikkim Himalaya - Lomash Sharma; Rajesh Kumar; Kime Tare; Sandhya Lamichaney (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Towards water-resilient cities: exploring rain gardens as urban flood mitigation in Delhi - Arup Babu; Apoorva Singh; Arkadip Mallik; Sandhya Rao; Ashvani Kumar Gosain; C T Dhanya (Journal of Earth System Science, 2026)

Corrigendum to “Artificial intelligence-based solar radiation forecasting for efficient use of renewable power plants” [J. Atmos. Sol. Terr. Phys., 282 (2026), 106786] - Vishal Sorathiya; Sanjeev Kumar Mandal; Sandhya Umrao; Keerti Rai; Pavan Chaudhary; Sumitra Padmanabhan (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Standardization of in vitro regeneration and genetic transformation protocol in Nerium oleander L. - Sandhya Prajapati; Renu Nimoriya; Rosani Kumari Shaw; Carol Janis Bilung; Anjum Bano; Dipak Kumar Mishra; Vineeta Tripathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Artificial intelligence-based solar radiation forecasting for efficient use of renewable power plants - Vishal Sorathiya; Sanjeev Kumar Mandal; Sandhya Umrao; Keerti Rai; Pavan Chaudhary; Sumitra Padmanabhan (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Investigation of Atmospheric Boundary Layer Dynamics Over the Himalayan Foothill Region: Insights from Ground-Based LiDAR Observations and WRF Model - Shuchita Srivastava; Sandhya Singh; Som Sharma; Pooja Jindal; C. Aparna; Yogesh Kant; Debashis Mitra; Dharmendra Kumar Kamat; Aniket Patel; R. P. Singh; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Comparative evaluation of larval susceptibility of Culex quinquefasciatus and Culex gelidus to three formulations of Bacillus thuringiensis var. israelensis - Sandhya Ananth; S. Mahalakshmi; V. Pranav; Dharani Govindasamy; Ashwani Kumar (International Journal of Tropical Insect Science, 2026)

Leveraging a tailor-made approach to enhance the kinetics of a native ureolytic bacterium, Sporosarcina pasteurii PS3A, for effective bio-cementation - Syamili Sarma; Sandhya Sekhar; Anil Kumar Mishra (Bioresource Technology, 2026)

Rice yields and climate change: impacts and adaptation in Southern India - Sandhya Neelima Atla; Anantha Rama Rao Chitiprolu; Nirmal Ravi Kumar Kotamraju; Srinivasa Rao Vatluri; Rama Devy Mulpuri (Theoretical and Applied Climatology, 2026)

Genetic and genomic resources of Vigna species for their utility in advanced breeding - Kuldeep Kumar; Sudhir Kumar Jha; B. Manu; Adarsh Kumar; Vaibhav Kumar; Khela Ram Soren; Meenal Rathore; Sandhya Sharma; Kishor Gaikwad (Biologia Futura, 2026)

Mitigation of chromium toxicity in Ocimum basilicum L. under the synergistic impact of biochar and Trichoderma yunnanense (NBRICRF_97) - Priya Dubey; Aditi Roy; Sandhya Mishra; Sampurna Nand; Mariya Naseem; Ruchi Chauhan; Alvina Farooqui; Anju Patel; Puja Khare; Pankaj Kumar Srivastava (Physiology and Molecular Biology of Plants, 2026)

Cultural, pathogenic and genetic variability of Rhizoctonia solani isolates incitant of rice sheath blight disease - Y. Sandhya; M. Reddi Kumar; P. Madhusudhan; P. Sudhakar; P. Lavanya Kumari (Vegetos, 2026)

First report of the fiery box jellyfish Morbakka virulenta (Kishinouye, 1910) in Indian waters identified through integrative taxonomy - Ajay Kumar Jena; R. Amal; S.V. Sandhya; M. Aparna; Biraja Kumar Sahu (Regional Studies in Marine Science, 2026)

Genomic Characterization of F-box Genes in Pigeonpea (Cajanus cajan (L.) Millspaugh): Insights into Evolution, Synteny, and Spatio-Temporal Expression During Ovule/Seed Development - Kumari Arpita; Sandhya Sharma; Arvind Kumar Yadav; Machindra Nirgude; Mohammad Israil Ansari; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Assessment of genetic diversity and population structure analysis in Himalayan garlic genotypes from Sikkim using SSR markers - Lomash Sharma; Rajesh Kumar; Kime Tare; Sandhya Lamichaney (Molecular Biology Reports, 2025)

Effect of explant sources, sonication combined with vacuum infiltration, and biochar on improving Agrobacterium-mediated transformation efficiency in Eucalyptus camaldulensis - M. C. Sandhya; Sreeja Sahadevan; Krishnaraj Shamili; Manoj Kumar Rajendran; Harshita Singh; Aiyar Balasubramanian; Muthukrishnan Arun; Sivakumar Veerasamy; Mathish Nambiar-Veetil (Plant Biotechnology Reports, 2025)

Delving into the BURP Super family: A Comprehensive QTL-Assisted Study on RD22 genes and its Role in Salinity Stress Tolerance in Chickpea - Sandhya Tripathi; Chellapilla Bharadwaj; Maloti Hembram; Neeraj Kumar; Aravind K. Konda; B. Mondal; N. C. Gupta; G. P. Dixit; K. R. Soren (Biochemical Genetics, 2025)

Development of Or-gene-based co-dominant markers and their utilization in marker-assisted breeding for ß-carotene biofortification in different maturity groups of cauliflower - Shrawan Singh; Vinay Verma; Bhagchand Shivran; Rahul Kumar Meena; Anamika Chandel; Sandhya Saroha; Navinder Saini (Theoretical and Applied Genetics, 2025)

Soil bacterial diversity and its functions shift under varying chromium concentration in tannery waste dumpsite - Sandhya Mishra; Priyamvada Mishra; Priya Dubey; Mariya Naseem; Anju Patel; Meher H. Asif; Pankaj Kumar Srivastava (Environmental Sustainability, 2025)

Assessing ecological sustainability of the Narmada River using the macrophyte river index - Sandhya Saini; Tarun Kumar Thakur; Saebugari Balaswamy; Amit Kumar; Ramesh Raj Pant; Rupesh Kumar; Mohammad Rafe Hatshan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Amino acid metabolism in cervical cancer: Mechanisms and implications in therapy - Roopak Murali; Sivapriya Singaraj; Isha Govindh; Pooja Singh; Sandhya Sundaram; Satish Srinivas; Gopal Gopisetty; Harish C. Chandramoorthy; Rajesh Kumar Gandhirajan (Next Research, 2025)

Simulation study of effect of absorber layer thickness and ambient temperature on photovoltaic performance of CZTSe solar cells - Vikas Kumar Rajput; Rashmi; Sandhya Mann; A.S. Mathur; B.P. Singh (Next Research, 2025)

Two Evolutionary Diverged Liverworts that Shared the Same Habitats Developed a Few Distinct Seasonal Adaptive Strategies: Insights from a Transcriptomic Approach - Suvajit Basu; Sandhya Yadav; Vishal Kumar Jha; Subhankar Biswas; Akanksha Srivastava; Kritika Tripathi; Raju Mondal; Neha Chaurasia; Sushil Kumar Singh; Yogesh Mishra (Plant Molecular Biology Reporter, 2025)

Genomics data reveals DNA polymorphism associated with seed number per pod (SNPP) in pigeonpea, Cajanus cajan (L.) Millsp. - Akash Paul; Kuldeep Kumar; Machindra Nirgude; Antara Das; Sandhya Sharma; Kishor Gaikwad (The Nucleus, 2025)

Unveiling the Spatio-Temporal Dynamics of Son Beel: A Freshwater Wetland from Indian East Sub-Himalaya - Ganithi Sandhya; Subrata Nandy; Hitendra Padalia; Anisha Dey; Arun Jyoti Nath; Koushik Majumdar; Ashesh Kumar Das (Journal of the Indian Society of Remote Sensing, 2025)

Impact of home gardens promoted among urban residents in Dhaka, Bangladesh - Pepijn Schreinemachers; Sandhya S. Kumar; Nasir Md. Uddin (Food Security, 2025)
Promoting gardening among urban residents holds the potential to improve urban diets in low- and middle-income countries, but there is a lack of evidence of impact. This study tests the hypothesis that training urban residents in gardening increases their intake of fruit and vegetables. It uses panel data for 254 control and 425 treatment households from four city corporations in the Dhaka metropolitan area of Bangladesh. Urban residents, 85% of whom were women, were interviewed before the start of an urban gardening program and one year after training and inputs were provided to the treatment group. The study estimated the average treatment effects using a difference-in-difference estimator. Of the 38 outcomes tested, 20 are significant (p < 0.05) with 19 indicating a beneficial effect and one indicating an adverse effect. Among the beneficial effects, there is an increase in the diversity of fruits and vegetables produced (+ 5 species, p < 0.01), the frequency of harvesting (+ 0.64 times/week; p < 0.01), and increased sharing of produce with neighbors (+ 8%, p < 0.01). Regarding food and nutrition, there is an increase in women’s dietary diversity score (+ 0.37 on a 0–10 scale; p < 0.01), women’s minimum dietary diversity (+ 4%; p < 0.01), and in the number of portions of cooked vegetables eaten (+ 0.96 portions/day; p < 0.01). The gardening intervention also contributes to a range of perceived social, personal, and psychological benefits. The adverse effect is an increase in ultra-processed food consumption (+ 19%, p = 0.04). Nevertheless, the results confirm that urban gardening interventions can improve the quality of urban diets alongside other benefits.

Macrophages co-loaded with drug-associated and superparamagnetic nanoparticles for triggered drug release by alternating magnetic fields - Omkar Desai; Sandhya Kumar; Mario Köster; Sami Ullah; Sushobhan Sarker; Valentin Hagemann; Mosaieb Habib; Nicole Klaassen; Silke Notter; Claus Feldmann; Nina Ehlert; Hansjörg Hauser; et al. (Drug Delivery and Translational Research, 2025)
Two features of macrophages make them attractive for targeted transport of drugs: they efficiently take up a broad spectrum of nanoparticles (NPs) and, by sensing cytokine gradients, they are attracted to the sites of infection and inflammation. To expand the potential of macrophages as drug carriers, we investigated whether macrophages could be simultaneously coloaded with different types of nanoparticles, thus equipping individual cells with different functionalities. We used superparamagnetic iron oxide NPs (SPIONs), which produce apoptosis-inducing hyperthermia when exposed to an alternating magnetic field (AMF), and co-loaded them on macrophages together with drug-containing NPs (inorganic–organic nanoparticles (IOH-NPs) or mesoporous silica NPs (MSNs)). We show that individual macrophages can take up both SPIONs and drug-loaded NPs efficiently, thereby generating drug-loaded cells susceptible to AMF-induced cell death. Macrophages co-loaded with SPIONs and drug-containing IOH-NPs spontaneously released the drugs at similar rates irrespective of the application of an AMF. Notably, while the spontaneous drug release from macrophages co-loaded with SPIONs and drug-associated MSNs was low, AMF exposure accelerated the drug release. Thus, AMF exposure of SPION/drug-MSN coloaded macrophages provides a simple strategy for trigger-controlled drug release since it does not require any chemical modification of NPs or drugs. Thus, we assume that the coloading of different types of NPs will expand the potential of macrophages for drug delivery. Graphical Abstract

Description of Stieleria mannarensis sp. nov., isolated from a marine sponge, and proposal to include members of the genus Roseiconus in the genus Stieleria - Nicolai Kallscheuer; Gaurav Kumar; Shabbir Ahamad; Sandhya Duddeda; Chintalapati Sasikala; Christian Jogler; Chintalapati Venkata Ramana (Antonie van Leeuwenhoek, 2025)
A pink-coloured, salt- and alkali-tolerant strain, JC639 T , was isolated from a specimen of the marine sponge Spheciospongia sp. The novel isolate is motile, aerobic and forms oval to pear-shaped cells. It shares the highest 16S rRNA gene sequence identity with Stieleria neptunia Enr13 T and Stieleria maiorica Mal15 T in the family Pirellulaceae (phylum Planctomycetota ). Optimum pH and temperature for growth are 8.0 (range 7.0–10.0) and 25 °C (range 10–30 °C), respectively. Major fatty acids are C 15:1 ω8c, C 16:0, C 18:1 ω9c, C 18:0 , and C 16:1 ω7c/C 16:1 ω6c. Major polar lipids are phosphatidylcholine and phosphatidylethanolamine. The genome of strain JC639 T has a size of 9.56 Mb and a DNA G + C content of 59.5%. The polyphasic analysis of the isolate supports its delineation from the known species in the genus Stieleria . We therefore introduce Stieleria mannarensis sp. nov., represented by JC639 T (= KCTC 72168 T = NBRC 113878 T ) as the type strain. Based on an analysis of established phylogenomic markers performed with all current members of the overlapping genera Stieleria and Roseiconus , we further propose to include the two so far characterized Roseiconus species in the genus Stieleria .

CRISPR/Cas9: efficient and emerging scope for Brassica crop improvement - Shiv Shankar Sharma; Ashwani Pandey; Anamika Kashyap; Lakshay Goyal; Pooja Garg; Ranjeet Kushwaha; Jyoti Sharma; Shikha Tripathi; Sujata Kumari; George Thomas; Malkhey Verma; Navin C. Gupta; et al. (Planta, 2025)

Potential regulation of cleistogamy in pigeonpea through jasmonic acid and bHLH transcription factor interactions - Palak Gupta; Harsha Srivastava; Kuldeep Kumar; Machindra Nirgude; Kumari Arpita; Jyothilakshmi Vadassery; Sandhya Sharma; Malik Zainul Abdin; Kishor Gaikwad (Plant Reproduction, 2025)

Evaluating terminal heat stress tolerance and genetic variation in emmer wheat (Triticum dicoccum L.) germplasm using morphological and molecular approaches - Meda Alekya; Jyoti Kumari; Jatin Tanwar; Preeti Jakhar; Abhijeet Mudhale; Sandhya Tyagi; Shivani Sharma; Neelu Jain; Jai Prakash Jaiswal; K. J. Yashavantha Kumar; Shailendra K. Jha (Euphytica, 2025)

A geospatial analysis of coal mine overburden reclamation: Land use, carbon stock, biomass, and soil genesis in chronosequence plantations - Tarun Kumar Thakur; Digvesh Kumar Patel; Sandhya Saini; Anita Thakur; Singam Laxmana Swamy; Sanjeev Bakshi; Amit Kumar; Fohad Mabood Husain; Rupesh Kumar (Journal of Geochemical Exploration, 2025)

Further enrichment of targeted indole alkaloids through root-derived culture systems from Alstonia scholaris (L.) R.Br. - Carol Janis Bilung; Priyanka Rawat; Ankit Saxena; Rosani Kumari Shaw; Sandhya Prajapati; Sanjeev K. Shukla; Sanjeev Kanojiya; Dipak Kumar Mishra (In Vitro Cellular & Developmental Biology - Plant, 2025)

Biochar for mitigating pharmaceutical pollution in wastewater: A sustainable solution - Sampurna Nand; Prem Prakash Singh; Swati Verma; Sandhya Mishra; Anju Patel; Siddharth Shukla; Pankaj Kumar Srivastava (Science of The Total Environment, 2025)

Micro-Phyto-assisted reduction of Hexachlorocyclohexane (HCH) contamination in soil: A sustainable solution to mitigate HCH pollution - Aditi Roy; Priya Dubey; Sandhya Mishra; Poornima Vajpayee; Suchi Srivastava; Pankaj Kumar Srivastava (International Biodeterioration & Biodegradation, 2025)

Production of non-embryogenic synthetic seeds for short-term cold storage and ISSR marker-assisted genetic fidelity analysis of Coleus forskohlii (Willd) Briq. plants - Mahesh Kumar Badhepuri; Mahender Aileni; Prabhakar Rao Beeravelli; Sathish Kumar Durgam; Dulam Sandhya; Mahipal S. Shekhawat; Nageswara Rao Singisala (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Identifying the pollution sources of River Yamuna through field observations and participatory approach - Sayantan Samui; Arkadip Mallik; Dinesh Kumar; Sandhya Rao; C T Dhanya; Ashvani Kumar Gosain (Journal of Earth System Science, 2025)

Morphometric indices assessment: Implications for active tectonics in the upper Narmada Basin, central India - Digvesh Kumar Patel; Tarun Kumar Thakur; Sandhya Saini; Adesh Patel; S.C. Bhatt; Amit Kumar; Rupesh Kumar; Fohad Mabood Husain (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A paradigm assessment of low-cost ceramic membranes: Raw materials, fabrication techniques, cost analysis, environment impact, wastewater treatment, fouling, and future prospects - K.V.V. Satyannarayana; Randeep Singh; S. Lakshmi Sandhya Rani; M. Sreekanth; Vinoth Kumar Raja; Young-Ho Ahn (Journal of Water Process Engineering, 2024)

Understanding the role of P-type ATPases in regulating pollen fertility and development in pigeonpea - Rishu Jain; Harsha Srivastava; Kuldeep Kumar; Sandhya Sharma; Anandita Singh; Kishor Gaikwad (Molecular Genetics and Genomics, 2024)

Perspective Evaluation of Synthetic Biology Approaches for Effective Mitigation of Heavy Metal Pollution - Sandhya Mishra; Anju Patel; Pankaj Bhatt; Shaohua Chen; Pankaj Kumar Srivastava (Reviews of Environmental Contamination and Toxicology, 2024)

“Efficient novel fungal-enriched biochar formulation for hexavalent chromium bioremediation” - Priya Dubey; Aditi Roy; Sandhya Mishra; Mariya Naseem; Alvina Farooqui; Anju Patel; Poonam C. Singh; Pankaj Kumar Srivastava (Journal of Environmental Management, 2024)

A kinetic modelling approach to explore mechanism of Cr(VI) detoxification by a novel strain Pseudochrobactrum saccharolyticum NBRI-CRB 13 using response surface methodology - Sandhya Mishra; Priya Dubey; Mariya Naseem; Saloni Rishi; Anju Patel; Pankaj Kumar Srivastava (World Journal of Microbiology and Biotechnology, 2024)

Metformin augments major cytoplasmic organization except for spindle organization in oocytes cultured under hyperglycemic and hyperlipidemic conditions: An in vitro study - Amrutha Nedumbrakkad Kunnath; Shravani Kanakadas Parker; Daphne Norma Crasta; Jyolsna Ponnaratta Kunhiraman; Vanishree Vasave Madhvacharya; Sandhya Kumari; Guruprasad Nayak; R. Vani Lakshmi; Prashanth Kumar Modi; Thottethodi Subrahmanya Keshava Prasad; Anujith Kumar; Ayush Khandelwal; et al. (Toxicology and Applied Pharmacology, 2024)

An in vitro model of adipose tissue-associated macrophages - Karishma Bhatia; Sandhya Tiwari; Vikas Kumar Gupta; Neerav M Sapariya; Sanjeev K Upadhyay (Journal of Biosciences, 2024)

Comparison of Relative Activity versus Relative Expression Factors (RAF versus REF) in Predicting Glucuronidation Mediated Drug Clearance Using Recombinant UGTs - Sandhya Subash; Deepak Ahire; Mitesh Patel; Sahil Shaikh; Dilip Kumar Singh; Sujal Deshmukh; Bhagwat Prasad (Pharmaceutical Research, 2024)

Identification of superior haplotypes for flowering time in pigeonpea through candidate gene-based association study of a diverse minicore collection - Kuldeep Kumar; Anita Kumari; Kumar Durgesh; Amitha Mithra Sevanthi; Sandhya Sharma; Nagendra Kumar Singh; Kishor Gaikwad (Plant Cell Reports, 2024)

Introducing reverse Multi Influencing Factor technique in DRASTIC model for groundwater vulnerability assessment - Sandhya Ganwer; Manish Kumar Sinha; Amit Prakash Multaniya; Nikhil Ghodichore (Groundwater for Sustainable Development, 2024)

Optimization of xylanase production by Bacillus sp. MCC2212 under solid-state fermentation using response surface methodology - Ruchika Siwach; Sandhya Sharma; Azmat Ali Khan; Amit Kumar; Sharad Agrawal (Biocatalysis and Agricultural Biotechnology, 2024)

Monitoring genetic transformation with RUBY visible reporter in Nicotiana tabaccum L. - Phanikanth Jogam; Vaishnavi Anumula; Dulam Sandhya; M. Manokari; Ajay Kumar Venkatapuram; V. Mohan Murali Achary; Mahipal S. Shekhawat; Venkataiah Peddaboina; Venkateswar Rao Allini (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Multifunctional characteristics of biosynthesized CoFe2O4@Ag nanocomposite by photocatalytic, antibacterial and cytotoxic applications - Sandhya Punyasamudram; Reddy Prasad Puthalapattu; Ayyappa Bathinapatla; Ravikumar Mulpuri; Suvardhan Kanchi; Putta Venkata Nagendra Kumar (Chemosphere, 2024)

Bioactive activity and safety analysis of Monascus red biopigment - Vishu Chaudhary; Priya Katyal; Jaspreet Kaur; Surekha Bhatia; Sandhya Singh; Anuj Kumar Poonia; Anil Kumar Puniya; António Raposo; Sunghoon Yoo; Heesup Han; Hmidan A. Alturki; Anil Kumar (Food Bioscience, 2024)

Technology development and challenges for the transformation of municipal solid waste into sustainable energy production - Tirath Raj; Sandhya Sompura; K. Chandrasekhar; Sushil Kumar Singh; Srinath Pandey; Lalit Kumar Singh; Manish Singh Rajput; Deepak Kumar; Shashi Kant Bhatia; Anil Kumar Patel; Reeta Rani Singhania (Biomass and Bioenergy, 2023)

Bryophytes as Modern Model Plants: An Overview of Their Development, Contributions, and Future Prospects - Sandhya Yadav; Suvajit Basu; Akanksha Srivastava; Subhankar Biswas; Raju Mondal; Vishal Kumar Jha; Sushil Kumar Singh; Yogesh Mishra (Journal of Plant Growth Regulation, 2023)

Sustainable phyco-fabrication of silver nanoparticles using Coelastrella terrestris and their multiple downstream applications - Sunita Choudhary; Geetanjali Kumawat; Manisha Khandelwal; Rama Kanwar Khangarot; Vishambhar Sangela; Mukesh Kumar; Sandhya Deora; Nitish Rai; Vinod Saharan; Harish (Biocatalysis and Agricultural Biotechnology, 2023)

High doses of clethodim-based herbicide GrassOut Max poses reproductive hazard by affecting male reproductive function and early embryogenesis in Swiss albino mice - Reyon Dcunha; Sandhya Kumari; Mohd Altaf Najar; Anjana Aravind; Keerthana Sandesh Suvarna; Ananda Hanumappa; Sadhana P. Mutalik; Srinivas Mutalik; Sneha Guruprasad Kalthur; G.K. Rajanikant; Sazada Siddiqui; Sulaiman Alrumman; et al. (Chemosphere, 2023)

The Phylogenetic Study of the CRISPR-Cas System in Enterobacteriaceae - Simran Krishnakant Kushwaha; Aryahi A. Kumar; Hardik Gupta; Sandhya Amol Marathe (Current Microbiology, 2023)

Development of immobilized novel fungal consortium for the efficient remediation of cyanide-contaminated wastewaters - Saloni Rishi; Ispreet Kaur; Mariya Naseem; Vivek Kumar Gaur; Sandhya Mishra; Suchi Srivastava; Harvinder Singh Saini; Pankaj Kumar Srivastava (Bioresource Technology, 2023)

Recent advances in Surface Plasmon Resonance (SPR) biosensors for food analysis: a review - Nevetha Ravindran; Sandhya Kumar; Yashini M; Rajeshwari S; Mamathi C A; Nirmal Thirunavookarasu S; Sunil C K (Critical Reviews in Food Science and Nutrition, 2023)

Answer to “Comments on “Regulation of Paraquat for wheat crop contamination” by Garg, Gupta, S. et al., https://doi.org/10.1007/s11356-022–20,816-8” - Sandhya Gupta; Navneet Kumar Garg; Kapila Shekhawat (Environmental Science and Pollution Research, 2023)

Population genetic research on the Spadenose shark, Scoliodon laticaudus (Chondrichthyes, Carcharhinidae), reveals the presence of two significantly differentiated clades along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; P. U. Zacharia; Shoba J. Kizhakudan; K. V. Akhilesh; Sujitha Thomas; Subal Kumar Roul; M. Muktha; Swati Priyanka Sen; G. B. Purushottama; Shikha Rahangdale; K. K. Bineesh; et al. (Marine Biodiversity, 2023)

Environmental Characterization of Two Ecologically Distinct Gangetic Oxbow Lakes using Zooplankton Taxonomic Indices Through Comparative Approach for Wetland Monitoring - Suman Kumari; Lianthuamluaia Lianthuamluaia; Uttam Kumar Sarkar; Mishal Puthiyottil; Gunjan Karnatak; Dharmendra Kumar Meena; Sandhya Kavitha Mandhir; Md Abul Hassan; Ashok Kumar Jaiswar; Anil Prakash Sharma; Basanta Kumar Das (Wetlands, 2023)

Exome sequencing and microarray identified a novel large exonic deletion in SYT2 gene in an ultra-rare case with recessive CMS type 7 - C. P. Ravi Kumar; Parag M. Tamhankar; Radhika Manohar; Sheetal Sharda; G. K. Madhavilatha; S. G. Thenral; Sandhya Nair; A. K. Bojamma (Journal of Genetics, 2022)

Optimization of Gibberellic Acid Production in Endophytic Bacillus cereus Using Response Surface Methodology and Its Use as Plant Growth Regulator in Chickpea - Nitin Baliyan; Sandhya Dhiman; Shrivardhan Dheeman; Sandeep Kumar; Naveen Kumar Arora; Dinesh Kumar Maheshwari (Journal of Plant Growth Regulation, 2022)

Regulation of Paraquat for wheat crop contamination - Sandhya Gupta; Navneet Kumar Garg; Kapila Shekhawat (Environmental Science and Pollution Research, 2022)

Formulating Ternary Inclusion Complex of Sorafenib Tosylate Using β-Cyclodextrin and Hydrophilic Polymers: Physicochemical Characterization and In Vitro Assessment - Mahipal Reddy Donthi; Siva Ram Munnangi; Kowthavarapu Venkata Krishna; Sandhya Amol Marathe; Ranendra Narayan Saha; Gautam Singhvi; Sunil Kumar Dubey (AAPS PharmSciTech, 2022)

Bacteriophage cocktails as antibacterial agents in crop protection - Nitin Baliyan; Sandhya Dhiman; Shrivardhan Dheeman; Vineet Kumar Vishnoi; Sandeep Kumar; Dinesh Kumar Maheshwari (Environmental Sustainability, 2022)

An insight into phytic acid biosynthesis and its reduction strategies to improve mineral bioavailability - Sandhya Sharma; Lalitha Hari Dharani AnandKumar; Anshika Tyagi; Mehanthan Muthumilarasan; Kuldeep Kumar; Kishor Gaikwad (The Nucleus, 2022)

Evaluation of the Bioefficacy and Insecticide Compatibility of Entomopathogens for Management of Whitefly (Hemiptera: Aleyrodidae) on Upland Cotton Under Laboratory and Polyhouse Conditions - Satish Kumar Sain; Dilip Monga; Sandhya Kranthi; Neelakanth S. Hiremani; Dipak T. Nagrale; Rishi Kumar; Surender Kumar Verma; Yenumula G. Prasad (Neotropical Entomology, 2022)

Identification, tissue specific expression analysis and functional characterization of arrestin gene (ARRDC) in the earthworm Eudrilus eugeniae: a molecular hypothesis behind worm photoreception - Sayan Paul; Sudalai Mani Dinesh Kumar; Sandhya Soman Syamala; Subburathinam Balakrishnan; Vijithkumar Vijayan; Vaithilingaraja Arumugaswami; Sivasubramaniam Sudhakar (Molecular Biology Reports, 2022)

Seasonal Changes in the Antioxidative Defence System of a Liverwort Dumortiera hirsuta - Sandhya Yadav; Akanksha Srivastava; Subhankar Biswas; Suvajit Basu; Sushil Kumar Singh; Yogesh Mishra (Journal of Plant Growth Regulation, 2022)

Epigenetic regulation and autophagy modulation debilitates insulin resistance associated Alzheimer’s disease condition in rats - Violina Kakoty; Sarathlal K C; Sunil Kumar Dubey; Chih-Hao Yang; Sandhya Amol Marathe; Rajeev Taliyan (Metabolic Brain Disease, 2022)

Functional analysis of SCD1 gene involved in pathogenicity of spot blotch disease of wheat causing fungus Bipolaris sorokiniana - Kartar Singh; Rashmi Aggarwal; Praveen Kumar Verma; Sandhya Verma; Sapna Sharma; C. Manjunatha; Manoj Choudhary; Deepika Kulshreshtha; Kirti Rawat (Indian Phytopathology, 2022)

Sedimentological responses to coastal dynamics along the Thane District, North Maharashtra, West Coast of India - Sridhar D. Iyer; A. R. Gujar; V. Sanil Kumar; D. K. Naik; S. S. Gaonkar; Sandhya Naik; Pooja Shirodkar; F. Badesab; R. A. A. Luis (Sustainable Water Resources Management, 2021)

Mitochondrial COI based genetic diversity and phylogeographic structure of whitefly Bemisia tabaci (Gennadius) on cotton in India - Prabhulinga T; Sandhya Kranthi; Raghavendra K P; Rishi Kumar; Ruchika Suke; Shilpa Chawla; Keshav Raj Kranthi (International Journal of Tropical Insect Science, 2021)

Molecular characterization of SlATG18f in response to Tomato leaf curl New Delhi virus infection in tomato and development of a CAPS marker for leaf curl disease tolerance - Ashish Prasad; Gunaseelen Hari-Gowthem; Mehanathan Muthamilarasan; Zakir Hussain; Pawan Kumar Yadav; Sandhya Tripathi; Manoj Prasad (Theoretical and Applied Genetics, 2021)

Food selectivity and reproductive biology of small indigenous fish Indian river shad, Gudusia chapra (Hamilton, 1822) in a large tropical reservoir - Suman Kumari; Uttam Kumar Sarkar; Gunjan Karnatak; Sandhya Kavitha Mandhir; Lianthuamluaia Lianthuamluaia; Vikash Kumar; Debabrata Panda; Mishal Puthiyottil; Basanta Kumar Das (Environmental Science and Pollution Research, 2021)

Buffalo dung-inhabiting bacteria enhance the nutrient enrichment of soil and proximate contents of Foeniculum vulgare Mill - Sandhya Dhiman; Nitin Baliyan; Dinesh Kumar Maheshwari (Archives of Microbiology, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Recombinant expression of sericin-cecropin fusion protein and its functional activity - Dyna Susan Thomas; Chitra Manoharan; Sandhya Rasalkar; Rakesh Kumar Mishra; Ravikumar Gopalapillai (Biotechnology Letters, 2020)

Rational Design, Synthesis, and In Vitro Neuroprotective Evaluation of Novel Glitazones for PGC-1α Activation via PPAR-γ: a New Therapeutic Strategy for Neurodegenerative Disorders - Antony Justin; Subhankar Mandal; P. Prabitha; S. Dhivya; S. Yuvaraj; Pradeep Kabadi; Satheesh John Sekhar; C. H. Sandhya; Ashish D. Wadhwani; Selvaraj Divakar; Jeyabalan Jeyaram Bharathi; Priya Durai; et al. (Neurotoxicity Research, 2020)

Characterization of the olfactory system of the giant honey bee, Apis dorsata - Sandhya Mogily; Meenakshi VijayKumar; Sunil Kumar Sethy; Joby Joseph (Cell and Tissue Research, 2020)

Application of potassium-solubilising Proteus mirabilis MG738216 inhabiting cattle dung in improving nutrient use efficiency of Foeniculum vulgare Mill. - Sandhya Dhiman; Ramesh Chand Dubey; Nitin Baliyan; Sandeep Kumar; Dinesh Kumar Maheshwari (Environmental Sustainability, 2019)

New Record of Ariomma brevimanum (Klunzinger, 1884) (Perciformes: Ariommatidae) from Indian Waters - Subal Kumar Roul; Rajan Kumar; Shikha Rahangdale; Suraj Kumar Pradhan; Sandhya Sukumaran; Prathibha Rohit (Thalassas: An International Journal of Marine Sciences, 2019)

Actinomycin-Producing Endophytic Streptomyces parvulus Associated with Root of Aloe vera and Optimization of Conditions for Antibiotic Production - Sandhya Chandrakar; Ashwini Kumar Gupta (Probiotics and Antimicrobial Proteins, 2019)

Validation of QTL for grain weight using MAS-derived pairs of NILs in bread wheat (Triticum aestivum L.) - Supriya Kumari; Reyazul Rouf Mir; Sandhya Tyagi; Harindra Singh Balyan; Pushpendra Kumar Gupta (Journal of Plant Biochemistry and Biotechnology, 2019)

Insecticidal activity of botanical oils and other neem-based derivatives against whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) on cotton - Rishi Kumar; Sandhya Kranthi; V. S. Nagrare; D. Monga; Keshav Raj Kranthi; Naveen Rao; Amarpreet Singh (International Journal of Tropical Insect Science, 2019)

Studies on the Production of Broad Spectrum Antimicrobial Compound Polypeptide (Actinomycins) and Lipopeptide (Fengycin) from Streptomyces sp. K-R1 Associated with Root of Abutilon indicum against Multidrug Resistant Human Pathogens - Sandhya Chandrakar; Ashwini Kumar Gupta (International Journal of Peptide Research and Therapeutics, 2019)

Fish assemblage structure and spatial gradients of diversity in a large tropical reservoir, Panchet in the Ganges basin, India - Kavitha Mandhir Sandhya; Lianthuamluaia Lianthuamluaia; Gunjan Karnatak; Uttam Kumar Sarkar; Suman Kumari; Puthiyottil Mishal; Vikash Kumar; Debabrata Panda; Yousuf Ali; Bablu Kumar Naskar (Environmental Science and Pollution Research, 2019)

Comparative RNA editing profile of mitochondrial transcripts in cytoplasmic male sterile and fertile pigeonpea reveal significant changes at the protein level - Tanvi Kaila; Swati Saxena; G. Ramakrishna; Anshika Tyagi; Kishor U. Tribhuvan; Harsha Srivastava; Sandhya; Ashok Chaudhury; Nagendra Kumar Singh; Kishor Gaikwad (Molecular Biology Reports, 2019)

Understanding spatial and temporal patterns of fish diversity and assemblage structure vis-a-vis environmental parameters in a tropical Indian reservoir - Lianthuamluaia Lianthuamluaia; Puthiyottil Mishal; Debabrata Panda; Uttam Kumar Sarkar; Vikash Kumar; Kavitha Mandhir Sandhya; Gunjan Karnatak; Suman Kumari; Asit Kumar Bera; Subrata Das; Yusuf Ali (Environmental Science and Pollution Research, 2019)

Co-cultivation of siderophore-producing bacteria Idiomarina loihiensis RS14 with Chlorella variabilis ATCC 12198, evaluation of micro-algal growth, lipid, and protein content under iron starvation - Soundarya Rajapitamahuni; Pooja Bachani; Raj Kumar Sardar; Sandhya Mishra (Journal of Applied Phycology, 2019)

Population Status and Diurnal Behaviour of the Indian Flying Fox Pteropus giganteus (Brünnich, 1782) in Kathmandu Valley, Nepal - Sandhya Manandhar; Sanjan Thapa; Tej Kumar Shrestha; Rabindra Jyakhwo; Wendy Wright; Achyut Aryal (Proceedings of the Zoological Society, 2018)

Studies on the growth and mortality of Indian River shad, Gudusia chapra (Hamilton, 1822) from Panchet reservoir, India - Suman Kumari; Uttam Kumar Sarkar; Sandhya Kavitha Mandhir; Lianthuamluaia Lianthuamluaia; Debabrata Panda; Sushanta Kumar Chakraborty; Gunjan Karnatak; Vikash Kumar; Mishal Puthiyottil (Environmental Science and Pollution Research, 2018)

Identification and comparative analysis of Brassica juncea pathogenesis-related genes in response to hormonal, biotic and abiotic stresses - Sajad Ali; Zahoor Ahmad Mir; Anshika Tyagi; Javaid A. Bhat; Narayanappa Chandrashekar; Pradeep Kumar Papolu; Sandhya Rawat; Anita Grover (Acta Physiologiae Plantarum, 2017)

Withania coagulans tryptophan decarboxylase gene cloning, heterologous expression, and catalytic characteristics of the recombinant enzyme - Jyoti Singh Jadaun; Neelam Singh Sangwan; Lokesh Kumar Narnoliya; Sandhya Tripathi; Rajender Singh Sangwan (Protoplasma, 2017)

Preparation, characterization, and bio-efficacy evaluation of controlled release carbendazim-loaded polymeric nanoparticles - Sandhya; Sandeep Kumar; Dinesh Kumar; Neeraj Dilbaghi (Environmental Science and Pollution Research, 2017)

Analysis of SARAL/AltiKa Wind and Wave over Indian Ocean and its Real-time Application in Wave Forecasting System at ISRO - Suchandra Aich Bhowmick; Ruchi Modi; K. G. Sandhya; M. Seemanth; T. M. Balakrishnan Nair; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

Evaluating microbe-plant interactions and varietal differences for enhancing biocontrol efficacy in root rot disease challenged cotton crop - Santosh Babu; Ngangom Bidyarani; Preeti Chopra; Dilip Monga; Rishi Kumar; Radha Prasanna; Sandhya Kranthi; Anil Kumar Saxena (European Journal of Plant Pathology, 2015)

Comparative atom-based 3D QSAR study of 3-nitro-1H-1,2,4-triazole-based aliphatic and aromatic amines analogs for its anti-trypanosomal activities - Suresh Kumar; Ritesh Agrawal; Sandhya Bawa (Medicinal Chemistry Research, 2015)

Dominance of cyanobacterial and cryptophytic assemblage correlated to CDOM at heavy metal contamination sites of Gujarat, India - Shailesh Kumar Patidar; Kaumeel Chokshi; Basil George; Sourish Bhattacharya; Sandhya Mishra (Environmental Monitoring and Assessment, 2015)

Pseudomonas putida NBRIC19 provides protection to neighboring plant diversity from invasive weed Parthenium hysterophorus L. by altering soil microbial community - Sandhya Mishra; Puneet Singh Chauhan; Anil Kumar Goel; Ram Sanmukh Upadhyay; Chandra Shekhar Nautiyal (Acta Physiologiae Plantarum, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Design and synthesis of 2-chloroquinoline derivatives as non-azoles antimycotic agents - Suresh Kumar; Sandhya Bawa; Sushma Drabu; Bibhu P. Panda (Medicinal Chemistry Research, 2011)

Bioaccumulation of Metals in the Edible Catfish Heteropneustes fossilis (Bloch) Exposed to Coal Mine Effluent Generated at Northern Coalfield Limited, Singrauli, India - Sandhya Bharti; Tarun Kumar Banerjee (Bulletin of Environmental Contamination and Toxicology, 2011)

Designer promoter: an artwork of cis engineering - Rajesh Mehrotra; Gauri Gupta; Riccha Sethi; Purva Bhalothia; Narayan Kumar; Sandhya Mehrotra (Plant Molecular Biology, 2011)

Image representation, scaling and cognitive model of object perception - Sandeep Kumar Ganji; Indu Potula; Venkata Naga Pradeep Ambati; Bhujanga Rao; Sandhya Kumari Ganji; Shwetha Kumari Ganji (Cognitive Processing, 2006)